Potential Toxicity of Legundi Leaf Extract (Vitex Trifolia L) Using the Brine Shrimp Lethality Test (BSLT) Method - Arifah, Zil; Efdi, Mai; Syafrizayanti, Syafrizayanti (Journal of The Indonesian Society of Integrated Chemistry, 2024)
Many natural products can be used as starting points in developing modern medicines because of their capabilities in pharmacological activities. Vitex trifolia L is an herbal plant that has been used to treat diseases such as fever, inflammation, colds, irregular menstruation, and diseases related to the female reproductive organs. This study aims to identify the cytotoxic ability of Vitex trifolia L leaf extract using the Brine Shrimp Lethality Test (BSLT) method. Extraction was carried out by maceration and fractionation methods, followed by phytochemical assay and cytotoxic assay using BSLT method. The results showed that the n-hexane extract had a moderate cytotoxic effect (LC50 241 µg/ml), the methanol extract included in the low toxic category (LC50 995 µg/ml) and the other two extracts involved in the non-toxic category (ethyl acetate and butanol).